Lean Approach of Pharmaceutical Installations At Hospital ABC Purbalingga to Increase Pharmacy Service Efficiency - Rani Aulia Imran (Journal of Industrial Engineering and Halal Industries, 2022)
A good pharmacy quality services are intended to the pharmaceutical product which is well prepared, stored, distributed, dispensed and discarded. However, these days services are assessed through medication availability, waiting time and user satisfaction. Therefore, hospitals need to make continuous quality improvements to the process of service, facilities, utilities, and health workers. This research aims to propose improvements to hospital pharmacy services quality by using Lean approaches in reducing services waiting time of concoction medicine. A case study was at Hospital ABC at Central Java, conducted in February-April 2019. There is a crucial problem was the prescription drug waiting time of concoction medicine. This study begins with process flow analysis and waste identification by interviewing with stakeholders of the hospital. Non-value added and value-added activities been divided, then time measurement in each activity is carried out with a time study method, to get the actual time of compounding the drug. Current state flow was mapped using value stream mapping tools, and future state flow map was recommended. Using lean tools, value-added activities have been identified and process time in future state map optimized to 47%. By using 5-why’s root cause analysis, problems identified and improvement of visual management were recommended.